2007
DOI: 10.1210/en.2006-0974
|View full text |Cite
|
Sign up to set email alerts
|

Steroid and G Protein Binding Characteristics of the Seatrout and Human Progestin Membrane Receptor α Subtypes and Their Evolutionary Origins

Abstract: A novel progestin receptor (mPR) with seven-transmembrane domains was recently discovered in spotted seatrout and homologous genes were identified in other vertebrates. We show that cDNAs for the mPR ␣ subtypes from spotted seatrout A LTHOUGH THE IMPORTANCE of rapid (i.e. nonclassical) steroid actions initiated at the cell surface through binding to steroid membrane receptors has become more widely accepted within the past few years, details of the initial steroid-mediated events, including the identities of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
260
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(294 citation statements)
references
References 50 publications
15
260
1
3
Order By: Relevance
“…However, while some recent reports have also suggested that steroid reception may occur at the cell membrane in certain animal systems (Thomas et al 2007), preliminary searches of animal genome databases do not reveal BRI1-like sequences. Further, receptor sequences similar to those in animals have not been found in plants (Clouse 2002).…”
Section: Br Signallingmentioning
confidence: 89%
“…However, while some recent reports have also suggested that steroid reception may occur at the cell membrane in certain animal systems (Thomas et al 2007), preliminary searches of animal genome databases do not reveal BRI1-like sequences. Further, receptor sequences similar to those in animals have not been found in plants (Clouse 2002).…”
Section: Br Signallingmentioning
confidence: 89%
“…Although mPR binds P 4 with high selectivity and affinity, it does not bind many of the synthetic progestins including norethisterone, norgestrel, promesgestrone, and demegestone [83]. This differential binding may underlie the distinct differences in neuroprotection and MAPK activation elicited by P 4 and synthetic progestins [10;11].…”
Section: Mechanisms Of Progesterone Actionmentioning
confidence: 99%
“…The rest of the cells were treated with RIPA buffer and completed with protease inhibitors, which enables rapid and efficient cell lysis and solubilisation of proteins until subsequent Western blot assays. Both techniques were performed based on protocols previously described by Ndiaye et al, 18 Thomas et al 17 and Dosiou et al 16 RT-PCR results were analysed in a Light Cycler 480 (Roche Instruments). + T cells, the total number and percentages of the Treg cell subset within the total CD4 + CD25 high CD127 low population, and the total number and percentages of mPRa + Treg cells, and the MFI between the different women's characteristics (parity and gestational age) was determined.…”
Section: Real Time Pcr and Western Blot Analysismentioning
confidence: 99%